2022
DOI: 10.14814/phy2.15164
|View full text |Cite
|
Sign up to set email alerts
|

Boric acid transport activity of human aquaporins expressed in Xenopus oocytes

Abstract: Boron is an essential element in various organisms. The biological importance of boron was initially described in plants (Tanaka & Fujiwara, 2008;Warington, 1923). Boron deficiency influences the growth and expansion of plant organs, such as leaves, roots, flowers, fruits, and seeds, and boron availability is widely recognized as an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…TrAqp, Takifugu rubripes aquaporin; HsAqp, Homo sapiens aquaporin. Results of HsAqps were recalculated from our previous study (Ushio et al, 2022 ). Control 1 and 2 indicate results of water‐injected oocytes in this and the previous study, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TrAqp, Takifugu rubripes aquaporin; HsAqp, Homo sapiens aquaporin. Results of HsAqps were recalculated from our previous study (Ushio et al, 2022 ). Control 1 and 2 indicate results of water‐injected oocytes in this and the previous study, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Boric acid (B(OH) 3 ) is in equilibrium with borate (B(OH) 4 − ) in aqueous solutions. To determine which form is transported in oocytes expressing TrAqps, B(OH) 3 or B(OH) 4 − , we analyzed changes in intracellular pH (pH i ) of oocytes expressing TrAqps in a solution containing boric acid because B(OH) 3 influx elicits intracellular acidification, but the influx of B(OH) 4 − elicits intracellular alkalization and membrane hyperpolarization (Kato et al, 2022 ; Ushio et al, 2022 ). Changes in pH i were analyzed in oocytes expressing TrAqp3a, 7, 8bb, 9a, and 9b in an iso‐osmotic solution containing boric acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we analyzed the boric acid transport activity of human AQPs and showed that AQP3, AQP7, AQP8, AQP9, and AQP10 act as boric acid transport systems, likely as B(OH) 3 channels, based on the following evidence: (1) boric acid elicited a marked “decrease” in pH i but did not elicit a change in membrane potential in Xenopus oocytes expressing these AQPs and (2) boric acid altered intracellular boron content in Xenopus oocytes expressing these AQPs ( 63 ). The results showed that the B(OH) 3 transport activities of AQP3, AQP7, AQP8, AQP9, and AQP10 are electroneutral, suitable for the facilitated diffusion of B(OH) 3 across the plasma membrane, and contrast with the electrogenic boric acid transport activity of Slc4a11A.…”
Section: Discussionmentioning
confidence: 99%